Coreopsis bakeri (Asteraceae; Coreopsideae), a new species from Florida, USA - Schilling, Edward E.; Johnson, Ann F.; Iacona, Gwenllian D. (Phytotaxa, 2015)
Coreopsis bakeri (Asteraceae; Coreopsideae), an early blooming and very narrow-leaved perennial restricted to rare limestone glade habitats in northern Florida, is described as new. The plants most closely resemble Coreopsis lanceolata, a common species of the southeastern U.S., but have narrower, glabrous, and infolded leaves. In addition to phenotypic differences, the two species show divergence at two nuclear genes, the nuclear ITS and ETS regions, and for two chloroplast intergenic spacers (psbA-trnH and rpl32-trnL). Because of the rarity of C. bakeri and the very limited extent of its distinctive habitat, this species is in urgent need of protection. In addition, C. lanceolata is found in open areas near the limestone glades, and poses a potential threat through competition or hybridization.